2020
DOI: 10.3390/su12125053
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence for Romania Regarding Dynamic Causality between Military Expenditure and Sustainable Economic Growth

Abstract: Military spending and sustainable economic development have been widely discussed in recent decades. Especially in Romania, the defense budget is valued at $4.8 billion, registering a compound annual growth rate (CAGR) of 23.57%. It is also expected to reach $7.6 billion in 2023, according to a report by Strategic Defense Intelligence. There is no consensus in current research and less attention is paid to Eastern European countries. Considering the significant increase in military spending in Romania in recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Similar classification of variables can be seen in (Bel and Elias-Moreno 2009;Dunne and Perlo-Freeman 2003;Dunne and Nikolaidou 2001;Odehnal and Neubauer 2020). In general, military expenditure decrease can be expected when economies experience economic downturn accompanied by relatively low security risks, which corresponded to the situation in the majority of European NATO member states during and immediately after the economic crisis (Holcner and Olejníček 2017;Odehnal and Neubauer 2015;Holcner 2019;Tao et al 2020).…”
Section: Literature Overviewsupporting
confidence: 55%
“…Similar classification of variables can be seen in (Bel and Elias-Moreno 2009;Dunne and Perlo-Freeman 2003;Dunne and Nikolaidou 2001;Odehnal and Neubauer 2020). In general, military expenditure decrease can be expected when economies experience economic downturn accompanied by relatively low security risks, which corresponded to the situation in the majority of European NATO member states during and immediately after the economic crisis (Holcner and Olejníček 2017;Odehnal and Neubauer 2015;Holcner 2019;Tao et al 2020).…”
Section: Literature Overviewsupporting
confidence: 55%
“…By assuming that military spending has a negligible impact on growth, especially over time. Tao et al (2020) investigated the causality link between economic growth and and military spending for Romania, while found adverse impact of of military outlay on growth between 1996-1999 and 2002-2004. On the contrary (Saba & Ngepah, 2020) for a panel of 35 African nations the results revealed no evidence of convergence in military spending and growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Economic growth results in higher consumption of electricity, fossil fuels, and natural assets, which are challenges to sustainable economic growth (Zhao et al 2016). A recent study reported that military expenditure in Romania had a negative impact on sustainable economic growth (Tao et al 2020). Investigating economic growth in Romania with a focus on EU business climate, Hatmanu et al (2020) revealed that, in the short run, the interest rate negatively influences economic growth, while the exchange rate influences it positively.…”
Section: Literature Reviewmentioning
confidence: 99%